An investigation into linguistic expressions of interpersonal meaning in the political speeches by hillary clinton - Nguyễn Thị Trang (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study investigates linguistic expressions of interpersonal meaning in political speeches by Hillary Clinton. The study focuses on analyzing the expressions of mood element, modality and pronoun system from twenty political speeches by Hillary Clinton. On the basic of corpus collected from 20 political speeches by Hillary Clinton, the mood element, modality and pronoun system are described and analyzed in order to help readers have more understandings on the interpersonal meaning in political speeches and how to make use of it effectively. More than 20 speeches including 150 samples extracted and collected from the Hillary Clinton‘s official website were used to build the thesis‘s analyzing. The findings reveal that the architecture of Hillary Clinton‘s speeches achieved her political purpose as well as fulfilled its interpersonal meaning not only by corresponding with its lexicogrammmar but also by considering the contextual factors. From the findings, some implications are put forward for the teaching and learning English for Vietnamese learners.